Dehumanised Gatekeeping and the Future of Media and Journalism - Jędrzejewski, Stanisław (Roczniki Kulturoznawcze, 2024)
This article presents an analysis of the evolution of gatekeeping in the media, against the background of technological developments, in particular artificial intelligence (AI). The traditional gatekeeping model, based on the selection of information by editors or institutions, is being transformed in the face of digitisation and the democratisation of access to digital platforms. Contemporary media are moving from centralised information filtering towards a model where users and algorithms become the new gatekeepers of information, enabling the widespread sharing of content. This paper examines the implications of introducing AI into editorial processes, demonstrating both the potential benefits and risks associated with the automation of journalism. Three development scenarios of journalism changes . In the context of these developments, the author emphasises the need to develop ethical and transparent practices for the use of AI in the media, professional education and the search for answers to ethical and legal questions related to AI’s new role as gatekeeper. This discussion demonstrates the complexity of the challenges and opportunities that digitisation brings to the field of media and journalism, encouraging further research into the growing impact of AI on the future of the industry.